(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
Organ donation cannot be mandatory in the view of the current system of organ donation in The United States due to several circumstances, and factors would cause failing the system if it was adopted. Comparing with some European countries, which adopted the presumed consent in its organs donation system, The United States has its own special system. And the first obstacle is the freedom of practicing religion. In this paper, when the mandatory term indicated, it means the presumed consent. And my point is that there is no doubt that the current organs donation system in The United States is not working as it should be… [1], and what I am saying is that the change from organ donation system, built on a volunteering option to a mandatory rules would not be possible, or will say raising the system to the mandatory level will not be possible, which mean the presumed consent system will not be possible.